Simulation analysis of DC motor based solar water pumping system for agriculture applications in Rural areas - Gurgi, Zeina K.; Abdalla, Ali I.; Hassan, Enas D. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Solar photovoltaic (PV) generators for agriculture purposes offer a practical alternative over traditional electricand diesel-based water pumps due to their low cost, sustainable and eco-friendly nature. These systems are suitable for remote locationsin case of unreachablepower grid. However,the operation of these generators is affected by various factor such weather statusThis article proposes a photovoltaic water pumping system (PVWPS) to drive a centrifugal pump using a permanent magnet DC motor (PMDC).  Additionally, a boost converter for extracting the maximum power from PV panels was used in the system and an Incremental conductance (IC) algorithm was chosen in the controller circuit. The system was implemented and investigated using MATLAB/Simulink at various irradiance values (i.e., 400, 600, 800 and 1000) w/m2. The results indicate that the efficiency of the proposed system is higher than 90% at all selected irradiance values proven that the integration of PV array with water pumping system without any energy storage devices is applicable at a daytime.